Associations of cardiorespiratory fitness and obesity parameters with blood pressure: fitness and fatness in youth Latin-American ethnic minority. Issue 5 (4th July 2022) - Álvarez, Cristian; Cadore, Eduardo; Gaya, Anelise Reis; Mello, Júlio Brugnara; Reuter, Cézane Priscila; Delgado-Floody, Pedro; Ramos-Sepúlveda, Jeison A.; Carrillo, Hugo Alejandro; Devia, Dirina González; Ramírez-Vélez, Robinson
ABSTRACT: Background: In spite of wide international evidence about cardiorespiratory fitness (CRF) and adiposity in association with cardiovascular disease, there is poor evidence about this relationship in schoolchildren of ethnic minorities. Aim: To examine the relationship between CRF and body composition on blood pressure (BP) in a sample of ethnic minority schoolchildren from three Latin-American countries. Material and methods: A descriptive cross sectional study of total n = 3866, mean age 12.5 (2.7) y [girls n = 1997, mean age 12.8 (2.8) y; boys n = 1869, mean age 12.2 (2.7) y] schoolchildren from three Latin-American countries (Colombia, Brazil, Chile). Main outcomes were CRF, body mass index (BMI), waist circumference, body fat percentage (%BF), and BP (systolic SB, diastolic BP, and mean arterial pressure (MAP). Results: In both sex, and after adjusting for covariates (age and ethnicity group), negative CRF by V ˙ O2 peak levels were associated with a higher body fatness parameters (BMI, WC, WHtR and %BF p <0.001), and blood pressure measures (systolic BP, diastolic BP, and MAP; p <0.001). A lower CRF (by V ˙ O2 peak) was associated with a higher BP in girls (systolic SB −0.15; −5.10 (0.30), diastolic BP −0.14; −4.43 (0.23), and MAP −0.15; −4.93 (0.26) at p <0.001), and boys (systolic SB −0.02; −0.85 (0.32), DB −0.07; −2.23 (0.23), and MAP−0.06; −1.89 (0.25 at p <0.001). There was a significant association between a 'high-CRF + low-%BF' with a lower systolic SB diff = − 9.6 [0.7], diastolic BP diff = − 11.0 [0.6]; and MAP level diff = − 10.6 [0.6] all p <0.001). There was a significant association between a 'high-CRF + low-BMI' with a lower systolic diff = − 10.3 [1.1], diastolic diff = − 11.2 [1.1], and MAP diff = − 10.9 [1.0] all p <0.001. Conclusion: A lower CRF is associated with a higher body fatness parameters, and higher BP levels in Latin-American ethnic schoolchildren. Abbreviators: %BF: Percentage of Body fat; BIA: Bioelectric impedance analysis; BMI: Body mass index; BP: Blood pressure; CRF: Cardiorespiratory fitness; CVD: Cardiovascular disease; LDL-cholesterol: SD: Standard deviation; WC: Waist circumference; WHtR: Waist-height to ratio; V ˙ O2 max: Maximal oxygen consumption; V ˙ O2 peak: Peak of oxygen consumption